Anxiety in the family: a genetically informed analysis of transactional associations between mother, father and child anxiety symptoms. (20th May 2019) - Ahmadzadeh, Yasmin I.; Eley, Thalia C.; Leve, Leslie D.; Shaw, Daniel S.; Natsuaki, Misaki N.; Reiss, David; Neiderhiser, Jenae M.; McAdams, Tom A.
Abstract : Background: Anxiety in parents is associated with anxiety in offspring, although little is known about the mechanisms underpinning these intergenerational associations. We conducted the first genetically sensitive study to simultaneously examine the effects of mother, father and child anxiety symptoms on each other over time. Method: Adoptive parent and child symptoms were measured at child ages 6, 7 and 8 years from 305 families involved in the Early Growth and Development Study, using a prospective adoption design. Children were adopted at birth to nonrelatives, and composite data on internalising problems within birth families were used as a proxy measure of offspring inherited risk for anxiety. Structural equation models were fitted to the data to examine prospective associations between adoptive mother, father and child symptoms, whilst accounting for individuals' symptom stability over time. Results: Child anxiety symptoms at age 7 predicted adoptive mothers' anxiety symptoms at age 8. No mother‐to‐child or child‐to‐father effects were observed. These results were consistent in sensitivity analyses using only paternal offspring reports and using a second measure of child anxiety symptoms. Fathers' anxiety symptoms at child age 6 prospectively predicted child symptoms, but only when paternal offspring reports were included in the model. Composite data on birth family internalising problems were not associated with child anxiety symptoms. Conclusions: Results show environmentally mediated associations between parent and child anxiety symptoms. Results support developmental theories suggesting that child anxiety symptoms can exert influence on caregivers, and mothers and fathers may play unique roles during the development of child symptoms. Further research is needed on the role of genetic transmission associated with anxiety symptoms in biologically related families. In the meantime, researchers and clinicians should strive to include fathers in assessments and consider the effects of child symptoms on caregivers.